(untitled) (Intent Research Scientific Journal, 2023)
This article, a socio-philosophical analysis of management models and a strategic approach to them is considered in Uzbekistan. The Uzbek model, the dialectical relationship of the movement strategy and the development strategy, and the systematic analysis of the laws of its manifestation are given.